2007
DOI: 10.1111/j.1365-2958.2007.05879.x
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic‐di‐GMP receptor required for bacterial exopolysaccharide production

Abstract: SummaryBis-(3Ј,5Ј)-cyclic-dimeric-guanosine monophosphate (c-di-GMP) has been shown to be a global regulatory molecule that modulates the reciprocal responses of bacteria to activate either virulence pathways or biofilm formation. The mechanism of c-di-GMP signal transduction, including recognition of c-di-GMP and subsequent phenotypic regulation, remain largely uncharacterized. The key components of these regulatory pathways are the various adaptor proteins (c-di-GMP receptors). There is compelling evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
419
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(442 citation statements)
references
References 57 publications
3
419
0
7
Order By: Relevance
“…While activating flagellum gene expression, FleQ represses pel transcription at low c-di-GMP levels (under planktonic, free-swimming growth conditions), with its inhibitory effect on pel transcription negated when intracellular c-di-GMP levels are high (60). Pel polysaccharide biosynthesis is furthermore regulated in P. aeruginosa by the c-di-GMP receptor protein PelD (91). Recently, a novel c-di-GMP protein that triggers attachment by inducing polysaccharide production was identified in V. cholerae (83).…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
“…While activating flagellum gene expression, FleQ represses pel transcription at low c-di-GMP levels (under planktonic, free-swimming growth conditions), with its inhibitory effect on pel transcription negated when intracellular c-di-GMP levels are high (60). Pel polysaccharide biosynthesis is furthermore regulated in P. aeruginosa by the c-di-GMP receptor protein PelD (91). Recently, a novel c-di-GMP protein that triggers attachment by inducing polysaccharide production was identified in V. cholerae (83).…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
“…A modified Congo red binding assay, described previously by Lee et al (2007), was used to assess the effect of CFS on pathogenic exopolysaccharide. The bacterial cells were collected after centrifugation, and resuspended in 1 mL LB broth containing Congo red (40 μg/mL) and 100 μL CFS derived from lactobacilli.…”
Section: Effect Of Cfs Derived From Lactobacilli On Pathogenic Extracmentioning
confidence: 99%
“…Another well-documented activity of cyclic di-GMP in P. aeruginosa is the induction of biofilm formation (Hickman et al, 2005;Lee et al, 2007). Elevated cellular levels of cyclic di-GMP increase the production of biofilm matrix components in P. aeruginosa including the Pel and Psl polysaccharides and a biofilm-associated adhesin (Hickman et al, 2005;Hengge, 2009;Borlee et al, 2010).…”
Section: Ml1419c Tpbb Ml1419cmentioning
confidence: 99%
“…To overcome these limitations, we chose to express ml1419c in an alternative heterologous host, P. aeruginosa PAO1, in which the effects of increasing and decreasing levels of cyclic di-GMP are well documented and control a range of phenotypes (Borlee et al, 2010;Hickman & Harwood, 2008;Hickman et al, 2005;Irie et al, 2012;Kulasakara et al, 2006;Merritt et al, 2007;Lee et al, 2007;Mills et al, 2011). Previously published studies have specifically shown that overexpression of the DGC encoded by tpbB (PA1120) increases cyclic di-GMP concentrations and corresponding biofilm formation in P. aeruginosa (Hickman & Harwood, 2008;Kulasakara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%